BATHYMETRIC-BASED SEDIMENTATION ASSESSMENT IN BALI’S VOLCANIC LAKES - Luh Ayu Putri Wedayanti Pulasari; I Dewa Ayu Meia Damayanthi; Ni Luh Putri Prabandari (Universitas Udayana, 2025)
The volcanic lakes of Bali, such as Batur, Beratan, Buyan, and Tamblingan, play a critical role in water provision, ecosystem services, and socio-cultural values. In addition to serving as raw water sources for irrigation, domestic use, dan tourism, these lakes also carry important conservation and spiritual functions embedded in Balinese cultural life. However, land-use changes, agricultural intensification, and tourism development within their catchments have accelerated erosion and sediment transport into the lakes. This sediment accumulation has resulted in lakebed shallowing and reduced storage capacity, thereby threatening the long-term sustainability of their hydrological and ecological functions. This study aims to examine sedimentation processes and potential shallowing through a 2024 bathymetric survey of Bali’s four main volcanic lakes. The analysis indicates an increase in sediment deposition between 2023 and 2024, with average thicknesses of 0.12 m in Lake Batur, 0.24 m in Lake Beratan, 0.49 m in Lake Buyan, and 1.56 m in Lake Tamblingan. Among these, Lake Tamblingan recorded the greatest thickness of sediment accumulation. These findings highlight the importance of regular monitoring of lake conditions. Bathymetric analysis can serve as a scientific basis for technical conservation planning, including dredging, upstream erosion control, and zoning of lake areas according to their vulnerability to sedimentation.